Counter-Pressure Practice Method by Spuses for Reducing Pain of Mothers In First Stage Labour - Sri Rejeki (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2016)
Abstract. Background. Pain in childbirth cause psychological disorders for mothers, such as 87% of postpartum blues, 10% of depression and 3% of psychosis. Therefore interventions to reduce labour pain is necessary to prevent complications in the mother and fetus during the process and after delivery. One method to reduce the pain of childbirth is to give counter pressure on the sacral region, but the application of this method is usually only done by health workers.Counter pressure method can be taught in the family, especially the spouse to reduce the pain of childbirth. Mother in labor need support from the environment of health care workers, families, especially spouses (husband). Objective: to describe the practice of counter pressure made by the husband and wife to relieve pain in labour. Research method: used descriptive analytic design. As the population were 40 husbands who waiting for their wifes at first stage of labour. The husbands have been trained about counter-pressure methods. The sampling method used consecutive sampling method.Results: obtained 75% husbands did well for practicing counter-pressure method, 60% women claimed reducing of pain after given counter- pressure by their husband. As a recommendation of this study is the importance of spouse presence in first stage labour for reducing the pain of mothers in childbirth.